"Ghana must Progress, but we are Really Suffering": Bui Dam, Antipolitics Development, and the Livelihood Implications for Rural People. Issue 6 (3rd June 2018) - Hausermann, Heidi
ABSTRACT: In late-2013, Bui Dam was commissioned on Ghana's Black Volta River. The hydroelectric project inundated 444 km 2, flooding communities, forests, crops, and a national park. State elites promoted the dam through nationalistic discourses while simultaneously framing rural people responsible for accessing its trickle-down economic benefits. Drawing from critical development literature within a political ecology framework, this article examines tensions between discourses underpinning construction of Bui Dam and the lived experiences of rural people. Drawing from data collected in 82 interviews, the dam's implications for resettlement, food security, mental health, agricultural production, and fishing livelihoods are detailed. I argue interlocking discourses, laws and processes—from eminent domain and compensation metrics to party politics—combined to work as an "antipolitics machine." Hydroelectric development renders invisible structural processes shaping inequality and creates new injustices. As Bui Power Authority, the corporation managing the dam and surrounding land-uses has a new CEO, the article concludes with several practical suggestions for improving community members' everyday lives.